CAPACITY BUILDING AND WOMEN-OWNED SMALL AND MEDIUM ENTERPRISES' (SMEs) PERFORMANCE: EMPIRICAL EVIDENCE FROM SOUTHWEST, NIGERIA - Sajuyigbe, Ademola Samuel; Eniola, Anthony Abiodun; Ayeni, Adebanji; Oladejo, Dauda Adewale (Journal of Business And Entrepreneurship, 2021)
Women entrepreneurs play a key role in national economies around the world, generate employment and value-added, and contributing to innovation. However, they have been marginalized, culturally excluded from having access to finance, networking, and social progress. This study, therefore, looks at the influence of capacity building on women-owned SMEs’ execution. Particularly, the study determines the influence of financial inclusion strategy, social inclusion strategy, entrepreneurial orientation strategy, and networking skills strategy on women-owned SMEs’ performance. The study adopts a quantitative methodology, and a structured questionnaire that contains an overwhelmingly closed-ended questionnaire was utilized to gather information for analysis purposes. Judgmental sampling procedures were utilized for information assortment, which is known as a nonprobability sampling procedure. Two hundred and twenty (220) questionnaires were recuperated out of three hundred (300) questionnaires dispersed, giving a recovery rate of 73.3%. Analysis of data was done via frequencies, percentages, correlation analysis, and ordinary least square. The results of the investigation reveal that capacity building components are major predictors of women-owned SMEs’ performance. The study also confirms that the capacity building of women entrepreneurs in SMEs through an array of skills in financing, culture re-orientation, risk-taking, and networking are strong predictors of women-owned SMEs’ performance. This development indicates that if women who represent virtually half of the Federal Republic of Nigeria population exploit their full potentials and remodel Nigeria from a developing country into an industrial nation by 2030, they must give the most extreme inclination to capacity building.